EVALUATION OF THE TROPHIC STATES OF MEDIO MUNDO’S MAIN LAGOON OF THE ALBUFERA REGIONAL CONSERVATION AREA, HUAURA-LIMA, PERU - Mendoza-Caballero, Wilfredo (2023)
Wetlands provide multiple ecosystem services that multiply the social, economic, and environmental development of the population; However, these problems undergo environmental problems that accelerate the eutrophication process. The purpose of this research was to evaluate the trophic states of Medio Mundo’s main lagoon of the Albufera Regional Conservation (ACRAMM). For this, the Carlson Trophic State Index modified by Toledo (IETM) was used and a predictive mathematical model for the total water phosphorus was formulated; where the dependent variable was represented by the parameter and the independent ones, by the reflections of Sentinel-2 images. The ACRAMM, according to the phosphorus model, was eutrophic on the first 5 dates evaluated (IETMPT> 65.56) and from oligotrophic to eutrophic with a tendency to increase from south to north on the last date (IETMPT = 38.29-56.99). These results lead to the conclusion that the trophic status of the ACRAMM is in the highest classification of the index, mainly by the following polluting sources: agricultural drainage, industrial wastewater dumping, open oxidation ponds at Medio Mundo town, grazing activities, tourist facilities and water pumping stations installed at adjacent areas.